The The Rightful Autonomy of The Priestly Fraternity Of Saint Peter (can. 586, 732 CIC/83) (Part I) - Pietras, Dawid (Prawo Kanoniczne, 2026)
The rightful autonomy of the life of an institute was expressed by the legislator in canon 586 of the CIC/83. According to this principle, each institute of consecrated life and society of apostolic life has the right, and even the obligation, to maintain its own discipline and patrimonium. Local Ordinaries should also show concern for preserving this charism. This principle also applies to the Priestly Fraternity of Saint Peter (FSSP), which was erected in 1988. The charism of this congregation is to preserve the liturgical and disciplinary traditions of 1962, while remaining in full communion with the Roman Pontiff. The charism of this clerical society of apostolic life of the pontifical right has been expressed in decrees issued by the Pontifical Commission Ecclesia Dei, the approved FSSP Constitutions, and Pope Francis’s decree of 11 February 2022. The conditions for realizing the rightful autonomy of the FSSP’s life are linked to universal law regarding a celebration of the ancient rites. This law was amended by the issuing of the papal motu proprio Summorum Pontificum of 2007 and Traditionis custodes of 2021, when the possibility of using the 1962 books of the Roman Rite was significantly limited.